The influence of a CYP1A2 polymorphism on the ergogenic effects of caffeine - Womack, C. J.; Saunders, M. J.; Bechtel, M. K.; Bolton, D.; Martin, M.; Luden, N. D.; Dunham, W.; Hancock, M. (Journal of the International Society of Sports Nutrition, 2012)
Although caffeine supplementation improves performance, the ergogenic effect is variable. The cause(s) of this variability are unknown. A (C/A) single nucleotide polymorphism at intron 1 of the cytochrome P450 (CYP1A2) gene influences caffeine metabolism and clinical outcomes from caffeine ingestion. The purpose of this study was to determine if this polymorphism influences the ergogenic effect of caffeine supplementation. Methods Thirty-five trained male cyclists (age = 25.0 +/- 7.3 yrs, height = 178.2 +/- 8.8 cm, weight = 74.3 +/- 8.8 kg, VO2max = 59.35 +/- 9.72 ml . kg-1 . min-1) participated in two computer-simulated 40-kilometer time trials on a cycle ergometer. Each test was performed one hour following ingestion of 6 mg . kg-1 of anhydrous caffeine or a placebo administered in double-blind fashion. DNA was obtained from whole blood samples and genotyped using restriction fragment length polymorphism-polymerase chain reaction. Participants were classified as AA homozygotes (N = 16) or C allele carriers (N = 19). The effects of treatment (caffeine, placebo) and the treatment x genotype interaction were assessed using Repeated Measures Analysis of Variance. Results Caffeine supplementation reduced 40 kilometer time by a greater (p < 0.05) magnitude in AA homozygotes (4.9%; caffeine = 72.4 +/- 4.2 min, placebo = 76.1 +/- 5.8 min) as compared to C allele carriers (1.8%; caffeine = 70.9 +/- 4.3 min, placebo = 72.2 +/- 4.2 min). Conclusions Results suggest that individuals homozygous for the A allele of this polymorphism may have a larger ergogenic effect following caffeine ingestion.